The focal adhesion-localized CdGAP regulates matrix rigidity sensing and durotaxis. - Duncan B Wormer (Public Library of Science (PLoS), 2014)
Motile cells are capable of sensing the stiffness of the surrounding extracellular matrix through integrin-mediated focal adhesions and migrate towards regions of higher rigidity in a process known as durotaxis. Durotaxis plays an important role in normal development and disease progression, including tumor invasion and metastasis. However, the signaling mechanisms underlying focal adhesion-mediated rigidity sensing and durotaxis are poorly understood. Utilizing matrix-coated polydimethylsiloxane gels to manipulate substrate compliance, we show that cdGAP, an adhesion-localized Rac1 and Cdc42 specific GTPase activating protein, is necessary for U2OS osteosarcoma cells to coordinate cell shape changes and migration as a function of extracellular matrix stiffness. CdGAP regulated rigidity-dependent motility by controlling membrane protrusion and adhesion dynamics, as well as by modulating Rac1 activity. CdGAP was also found to be necessary for U2OS cell durotaxis. Taken together, these data identify cdGAP as an important component of an integrin-mediated signaling pathway that senses and responds to mechanical cues in the extracellular matrix in order to coordinate directed cell motility.